Cured : cooking with ferments, pickles, preserves, & more - McHugh, Steve, 1975-; Forbes, Paula (Ten Speed Press, 2024)
"Boost the flavor of any meal with this definitive guide on curing and preserving your own jams, pickles, sauces, and more, featuring more than 150 recipes for using your preserved goods"--